2010
DOI: 10.1002/pd.2648
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound probe pressure but not maternal Valsalva maneuver alters Doppler parameters during fetal middle cerebral artery Doppler ultrasonography

Abstract: Fetal MCA Doppler assessment is affected by increased probe pressure but not by maternal VM. Thus, the application of the MCA Doppler sonography should be undertaken in the head of fetuses without any probe pressure and without maternal VM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Fetal behavioral states influence the fetal cerebral hemodynamic pattern, with a significant decrease in MCA‐PI during fetal activity, this decrease being more marked in the proximal portion of the MCA. Variations in amniotic fluid volume and increased probe pressure have also been found to alter MCA measurements; singletons with polyhydramnios have significantly lower MCA‐PI than do those with normal amniotic fluid. Rizzo et al ,.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal behavioral states influence the fetal cerebral hemodynamic pattern, with a significant decrease in MCA‐PI during fetal activity, this decrease being more marked in the proximal portion of the MCA. Variations in amniotic fluid volume and increased probe pressure have also been found to alter MCA measurements; singletons with polyhydramnios have significantly lower MCA‐PI than do those with normal amniotic fluid. Rizzo et al ,.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation would be to assume the increase of MCA PI and RI as a consequence of increased fetal intracranial pressure when applying external pressure with the transducer. In case of increased intracranial pressure, vessel caliber is reduced, leading to high peripheral vascular resistance and explaining the increase in Doppler indices in the MCA [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…A study performed on adults by Homburg et al has noted that in case of increased intracranial pressure, the MCA Doppler parameters are modified [9]. At the same time, it was shown that the effect of maternal Valsalva maneuver did not alter the parameter values [10].…”
Section: Introductionmentioning
confidence: 99%
“…During examination, a sonographic probe should touch the body gently because strong pressure can significantly increase RI, PI, and Vsyst and decrease Ved in MCA. But the Valsalva maneuver by mother doesn't affect Doppler parameters of blood flow in MCA [423]. Regarding prognosis and child management, the role of Doppler parameters of cerebral circulation as a complementary measurement in prenatal screening in fetal ventriculomegaly remains questionable.…”
Section: The Presence Of Bilateral Asymmetric Ventriculomegaly Characmentioning
confidence: 99%